The Convoluted Nature of the African Ivory Trade: Possible Solutions for Curbing the Destructive Nature of Poaching and Promoting Elephant Conservation - Williams, Jonah M. (Consilience, 2016)
The current nature of ivory and elephant conservation within Africa is extremely ambiguous and filled with much uncertainty. The purpose of this work is to objectively investigate the sources for this convoluted complexion, which stem from a wide variety of issues including (but not limited to) geopolitics, imperialism, governmental legitimacy, foreign policies, and present-day western influences. In addition, this work also considers certain ecological ramifications of the current illicit African ivory trade, and sheds light on not only the problems relating to direct poaching, but also extraneous pressures, both internal and external, which are causing a high demand for ivory. Through such analyses, this paper investigates possible solutions to lower poaching and stimulate conservation of the African Elephant, as well as relieve African nations of post-imperialistic stress, granting them increased autonomy on the matter.